The relation between structural features and electrochemical activity of MnO2 nanoparticles synthesized from a polyol-made Mn 3O4 precursor - Dias, Cristiane de A.; Santana, Henrique de; Nobre, Marcos Augusto Lima [UNESP]; Lopes, Mauro C. (Springer Nature, 2013)
A simple hybrid synthesis processing method was developed to synthesize γ-MnO2 nanocrystalline particles. The polyol method was modified by the addition of nitric acid in order to allow the synthesizing of single-phase Mn3O4 in a large scale. In the sequence, the acid digestion technique was used to transform Mn3O4 into γ-MnO2. Structural and morphological characterization was carried out by X-ray diffractometry, Infrared and Raman spectroscopy, thermogravimetric analysis, nitrogen adsorption isotherm, scanning electron microscopy, and transmission electron microscopy. The electrochemical properties were investigated by cyclic voltammetry and galvanostatic charge-discharge measurements. The synthesized material exhibits a specific capacitance of 125.1 F g-1 at a mass loading of 0.98 mg cm-2. The relation between structural features and electrochemical activity is discussed by comparing the synthesized material with commercial electrolytic manganese dioxide. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: De Wolff disorder; Microtwinning; Pseudocapacitance; Supercapacitors; Electrolytic manganese dioxides; Galvanostatic charge discharges; Infrared and Raman spectroscopy; Morphological characterization; Super capacitor; Alcohols; Cyclic voltammetry; Manganese; Manganese oxide; Scanning electron microscopy; Thermogravimetric analysis; Transmission electron microscopy; X ray diffraction analysis; Synthesis (chemical)